Radiation risk estimation from occupational medical imaging exposure in Malaysia - Yahaya, S. R. (Penerbit UTM Press, 2015)
Ionizing radiation has been increasingly applied in medicine and firmly established as an essential tool for diagnosis. There is high possibility for medical radiation workers to receive doses that are considerably higher than recorded by their dosimeters due to lack of knowledge about ionizing radiation, lack of training in radiation protection, and attitude of the workers themselves toward radiation protection. The purpose of this study is to estimate the radiation risk due to occupational exposure to ionizing radiation among medical diagnostic workers at hospitals in Malaysia. Also the objective is to determine the knowledge of occupational radiation exposure and radiation safety among the workers. The assessment was made based on the collective doses collected from film badge of the workers. The results of risk assessment show the mean annual collective effective dose based on type of X-ray procedure in this study was 5.445mSv, which is much lower compared to the whole body exposure dose limit, set by the ICRP Publication 60. A survey on knowledge of occupational radiation exposure and radiation safety was conducted using questionnaire and it was found that vast majority of respondents were aware of radiation safety with 91.3% answered the specific questions regarding radiation protection at workplace correctly. Unfortunately only 30.4% of the respondents fully understand the hazard they are exposed to. The study reveals that there is a critical need to educate not only medical radiation workers but also medical doctors and nurses to decrease unnecessary occupational exposure to radiation hazard.